Radar-Enabled Resource Allocation in 5G-V2X Sidelink Communication - Haider Shah, Syed Najaf; Martín-Sacristán, David; Ravelo, Carlos; Smeenk, Carsten; Schneider, Christian; Robert, Joerg (IEEE Conference on Intelligent Transportation Systems, Proceedings, ITSC, 2023)
Integrated Sensing and Communication (ISAC) has emerged as a key technology in future cellular networks as it allows the integration of radar sensing capabilities into mobile networks by sharing the same spectral and hardware resources. This paper discusses the integration of radar sensing capabilities into 5G Vehicle-to-Everything (V2X) sidelink communication to enable an ISAC-capable 5G- V2X system that requires high-precision radar sensing and highly reliable communication among vehicles and road infrastructure. To meet these requirements in a high-density environment where target objects are moving in close proximity to one another, a radio resource allocation algorithm, based on the sensing-based semi-persistent scheduling (SB-SPS) scheme, has been proposed that allocates additional available time and frequency (bandwidth) resources to the transmitting vehicle for high-resolution radar sensing. Further, to reduce the channel occupancy generated by the transmitting vehicle by occupying the additional resources to perform radar sensing tasks, the approach reserves only the communication resources for future transmissions. The proposed approach is evaluated through a set of performance metrics of both radar sensing and communication including the probability of detection, root mean squared error (RMSE) of range and velocity estimation of target objects under line-of-sight (LOS) conditions, and packet reception ratio. The simulation results demonstrate that the proposed approach allows each vehicle to perform radar sensing while maintaining good communication performance.
CRIS-Team Scopus Importer:2024-11-19
Keywords: ISAC; Resource Allocation; Sidelink; V2X